Neurexin‐1 regulates sleep and synaptic plasticity in Drosophila melanogaster. (19th August 2015) - Larkin, Aoife; Chen, Ming‐Yu; Kirszenblat, Leonie; Reinhard, Judith; van Swinderen, Bruno; Claudianos, Charles; Galizia, C. Giovanni
Abstract Neurexins are cell adhesion molecules that are important for synaptic plasticity and homeostasis, although links to sleep have not yet been investigated. We examined the effects of neurexin‐1 perturbation on sleep in Drosophila, showing that neurexin‐1 nulls displayed fragmented sleep and altered circadian rhythm. Conversely, the over‐expression of neurexin‐1 could increase and consolidate night‐time sleep. This was not solely due to developmental effects as it could be induced acutely in adulthood, and was coupled with evidence of synaptic growth. The timing of over‐expression could differentially impact sleep patterns, with specific night‐time effects. These results show that neurexin‐1 was dynamically involved in synaptic plasticity and sleep in Drosophila. Neurexin‐1 and a number of its binding partners have been repeatedly associated with mental health disorders, including autism spectrum disorders, schizophrenia and Tourette syndrome, all of which are also linked to altered sleep patterns. How and when plasticity‐related proteins such as neurexin‐1 function during sleep can provide vital information on the interaction between synaptic homeostasis and sleep, paving the way for more informed treatments of human disorders.